ANALISIS PENDAPATAN ASLI DAERAH DAN BELANJA DAERAH KABUPATEN KETAPANG SEBELUM DAN SESUDAH OTONOMI DAERAH - B61110053, DONI ANDRIAWAN (Jurnal Ekonomi Daerah (JEDA), 2015)
ABSTRACT Regional Autonomy are right, authority and duty of region to arranges and manages itself based on valid regulation. The region should do all of things thatÂ  they got,, the destination is for making government serving be nearer with publics, publics can control every fund of Regional Income easier.. besides that,, it can create healthy competition inter-Regional and push innovation. In implementation,, Ketapang Regency,, one of West Kalimantan Province is a part of Autonom Region as instruction of law No. 25 / 1956 about The Formation Regional Autonomy West Kalimantan Province, South Kalimantan and East Kalimantan, the result is unoptimal. One of The Reason is the Regency is not making his Regional Fund and Cost maximal yet. so that,, the writer to critise about THE Fund and Cost of Ketapanag Regency before and after Autonomy happen. So,, the writer gives the title of this assignment with â€œThe Analysis of Regional Fund and Cost in Ketapang Regency before and After Autonomy Happenâ€. The formulation of problem that I can analyse is Do regional autonomy can give effect of Regional Fund and Cost in Ketapang Regency?. The purpose of this research is to know and to analyse the condition of Regional Fund and Cost before anad after autonomy happen. The result of this research expected can give benefit for Regional Government as input and judgment to determine financial regional policy that related to Regional Fund and Cost and as reference for the next researcher. This research use Descriptive metode and Time Series Data (1998-2013), the source is secondary data from The Official of Regional Fund in Ketapang Regency. The analyse instrument of this research are decentralitation level of fiscal, the analyse of effectivity and Paired Sample T-Test. The conclution is the level of Fiscal Decentralitation before and after regional autonomy in Ketapang Regency is low. The contribution of Regional Fund after regional autonomy higher than before regional autonomy. It cause the differences of number Regional Cost is higher than before Regional Autonomy and the effect of Regional Autonomy about Regional Fund and Cost in Ketapang Regency.